2008
DOI: 10.1002/pat.1090
|View full text |Cite
|
Sign up to set email alerts
|

Novel efficient DOPO‐based flame‐retardants for PWB relevant epoxy resins with high glass transition temperatures

Abstract: Novel derivatives of 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) were obtained by a simple synthetic route and incorporated in epoxy resins, consisting of epoxy novolac (DEN 438), dicyandiamide (DICY), and fenuron. The thermal and fire‐retardant properties of DICY‐cured DEN 438 epoxy samples containing the novel DOPO‐based additives were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and the UL 94 test. The obtained results were compared to those of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 16 publications
4
94
0
Order By: Relevance
“…HQ was originally adapted for epoxy thermosets and exhibits prominent ame-retardant properties in the gas phase. [13][14][15] In addition, HQ can produce active POc radicals during its decomposition, which are capable of reacting with Hc and OHc radicals during the combustion process of the matrix to decrease heat release, prevent further oxidation and consequently suppress ame propagation. 16,17 Besides, the incorporation of HQ into polyurethane can improve the ame retardancy without changing the structure of the matrix, and there is no long-term migration phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…HQ was originally adapted for epoxy thermosets and exhibits prominent ame-retardant properties in the gas phase. [13][14][15] In addition, HQ can produce active POc radicals during its decomposition, which are capable of reacting with Hc and OHc radicals during the combustion process of the matrix to decrease heat release, prevent further oxidation and consequently suppress ame propagation. 16,17 Besides, the incorporation of HQ into polyurethane can improve the ame retardancy without changing the structure of the matrix, and there is no long-term migration phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The result can be attributed to the fact that the SPD-BS forms a carbonaceous char during combustion, which acts as a physical barrier to insulate heat from the flame and to retard the diffusion of combustible gases, thus improving the flame-retardant properties. 3,6,17,18 This result also indicated that incorporating SPD-BS is very effective in improving the flame retardancy of epoxy resins.…”
Section: Resultsmentioning
confidence: 65%
“…[1][2][3][4][5] Our group is interested in using the versatility of the phosphorus atom to rationally design organophosphorus compounds that could act as flame retardants. [6][7][8][9] 6H-dibenzo[c,e][1,2]oxaphosphinine 6-oxide (a) is a commercially available flame retardant. To broaden its scope of application, novel derivatives of (a) with tailored chemical structures are synthesized in our working group.…”
Section: Introductionmentioning
confidence: 99%